"The Poor Carer": Ambivalent Social Construction of the Home Care Worker in Elder Care Services. Issue 7 (3rd October 2019) - Timonen, Virpi; Lolich, Luciana
ABSTRACT: In this article, we examine the social construction of the home care worker from the perspective of various professionals in the elder care sector in Ireland. The research, using the Grounded Theory method, involved focus groups with 31 participants comprising health and social work professionals as well as care agency managers and policy planners. The social construction of the elder care worker is characterised by ambivalence. We connect the concept of ambivalence at the micro level of human relationships to structural factors that are driving the ambivalence. Ambivalence towards home care workers is shaped by structural factors including the precariousness of care work, the commodification of time, and the stipulated personalisation of services. The irreconcilable contrasts between portrayals of care workers as both 'good' and 'bad' are indicative of deep contradictions in the expectations that contemporary care systems direct at paid caregivers. Ambivalence arises from the commodified and dispensable status of care workers, and fundamental transformations in their training, working conditions and pay are required to move away from this ambivalence and towards care workers' equal status with professionals in the care sector.